Embedding positive psychology into curriculum to promote posttraumatic growth, psychological flexibility, and socio-emotional competencies in higher education - Chim, Kathleen; Lai, JoJo T. C.; Chan, Benjamin Tak Yuen (Frontiers in Psychology, 2024)
The benefits of positive psychology interventions (PPIs) have become increasingly popular. While there is an emerging evidence base on the effectiveness of applying positive psychology in curriculum as preventive, early mental health intervention for higher education students, little is known about the content and pedagogy in these promising courses. Objective: This article describes (a) the rationale for and development of a positive psychology course embedded into the curriculum that aims to foster posttraumatic growth, psychological flexibility, and socio-emotional competencies for higher education students; and (b) a mixed-method non-randomised pre-post study to evaluate the effectiveness of the positive psychology course in achieving positive participant outcomes. Methods: Higher education students from different disciplines will be enrolled to a general education course, "Positive Psychology and Personal Growth", where they will learn progressive topics and complete summative assessments related to key areas in positive psychology. In addition to lectures, participants will engage in constructivist-based experiential activities that are guided by research on PPIs (Seligman et al., 2009), life-design interventions (Savickas, 2015) and constructivist learning principles (Olsen, 1999). The primary outcome is posttraumatic growth, and the secondary outcomes are psychological flexibility, and socioemotional competencies. Expected Results: We hypothesised that after the curriculum-embedded PPI, participants will have significantly higher levels of posttraumatic growth, psychological flexibility, and socioemotional competencies. Results derived from the questionnaire survey will be supported by corroborating evidence identified from qualitative analysis of participants' summative assessments and follow-up semi-structured interviews on their perceptions of the present course. Discussion: The current study will fill in a gap in existing intervention research and practice in curriculum-embedded PPIs and promote research transparency and pedagogical advancement. The intervention provides guidance and recommendations for educators to consider embedding positive psychology into the formal curriculum as cost-effective, low-intensity, structured, and sustainable educational interventions for higher education students.